Microwave-assisted seed preparation for producing easily phase-transformed anatase to rutile. Issue 72 (25th September 2017) - Tang, Siyang; Zhang, Yaowen; Yuan, Shaojun; Yue, Hairong; Liu, Changjun; Li, Chun; Liang, Bin
Abstract : Microwave heating seeds were used for dilute titanyl sulfate hydrolyzing. The uniform metatitanic acid particles could transform to rutile easily. Abstract : Titanium dioxide, as one of the most important optical materials, is usually manufactured by the hydrolysis of titanyl salts, in which the seeds are a key to affect product properties. In the sulfate process, hydrolysis normally leads to anatase which is then converted to rutile in a high-temperature calcination with the help of a crystal transforming agent. In this work, the initial seeds were prepared through microwave heating and then the seeds were introduced to the hydrolysis of dilute titanyl sulfate solution. The results showed that the hydrolysis product had a narrower particle size distribution compared with traditional processes, and it was much more easily converted to rutile product under low-temperature calcination in the absence of a crystal transforming agent. The microwave effects on the seed preparation conditions were evaluated, and the kinetic behavior of the seeds in hydrolysis was also studied.